Estate and Capital Gains Taxation: Efficiency and Political Economy Consideration - Saku Aura (Center for Economic Studies and ifo Institute (CESifo), 2004)
In this paper a simple dynastic overlapping-generations model with homogeneous agents is used to analyze the optimal use of capital income tax, labor income tax and estate tax. The results of this analysis add to the conventional wisdom about capital income taxation: while it is true that in the long run the estate tax rate should be set to zero, it is also true that other capital income taxation is a usable policy tool even in the steady state. The other contribution of the paper is the building of a simple dynamic political economy model where the structure of capital taxes is determined. In a median-voter framework with no policy commitment, estate taxation is used too heavily as a capital-tax-revenue-collecting tool relative to the second-best optimum for the social planner.
Keywords: 330; capital income taxation; optimal taxation; political economy